2003
DOI: 10.1590/s1679-62252003000200006
|View full text |Cite
|
Sign up to set email alerts
|

Movement of Cichla species (Cichlidae) in a Venezuelan floodplain river

Abstract: In their native habitats of black- and clear-water Neotropical rivers, large predatory cichlids of the genus Cichla are an important food and recreational resource. Understanding patterns of movement for these species is necessary for effective management and conservation; however, no information is available on movement in natural fluvial populations. Therefore, we initiated a cooperative mark-recapture program with local sport-fishing groups to evaluate movement of Cichla in the Cinaruco River, Venezuela and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 17 publications
(20 reference statements)
1
56
0
Order By: Relevance
“…The genus Cichla is considered common in South American rivers and lakes with clear and dark water (Hoeinghaus et al, 2003) in Amazon basin, and is never found in turbid waters (Winemiller, 2001). In the Volta Grande Reservoir, Gomiero & Braga (2003a) observed higher capture rates for Cichla species between 9:00am and 3:00pm in seasons with higher temperatures (spring and summer) and on brighter days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Cichla is considered common in South American rivers and lakes with clear and dark water (Hoeinghaus et al, 2003) in Amazon basin, and is never found in turbid waters (Winemiller, 2001). In the Volta Grande Reservoir, Gomiero & Braga (2003a) observed higher capture rates for Cichla species between 9:00am and 3:00pm in seasons with higher temperatures (spring and summer) and on brighter days.…”
Section: Discussionmentioning
confidence: 99%
“…Their popularity has been the intentional introduction of Cichla species in diverse tropical and sub-tropical freshwater regions in the world, at times leading to the decrease of populations of native fish species (Winemiller, 2001). Peacock bass were introduced into regions such as Florida, Hawaii, Panama, Puerto Rico, and in Brazil, in the southeast (Hoeinghaus et al, 2003), midwest (Resende et al, 2008), northeast (Fontenele & Peixoto, 1979), and south (Kullander & Ferreira, 2006). Natural to the Araguaia and Tocantins River basins, C. kelberi was before identified as C. monoculus (Kullander & Ferreira, 2006), being found in many reservoirs in southeastern Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, illegal commercial netting has increased in the río Cinaruco (Hoeinghaus et al, 2003b). Netters target large-bodied taxa, including the two most common species in gill net sampling, H. armatus and S. kneri.…”
Section: P R O O F Smentioning
confidence: 99%
“…This is the case of peacock-bass species (Cichla), which have successfully colonized many Neotropical reservoirs. These fishes are native to the Amazon basin, and, under natural conditions, are found in littoral habitats of rivers and lakes where they feed upon small-sized fish (Jepsen et al, 1997;Winemiller, 2001;Hoeinghaus et al, 2003). In reservoirs, Cichla finds suitable habitats for feeding and breeding, considering that prey fish are abundant (Pelicice et al, 2005;Luz-Agostinho et al, 2006) and shallow areas provide shelter and nesting sites.…”
Section: Introductionmentioning
confidence: 99%